PENGARUH PENDAPATAN PEKERJA WANITA SEKTOR PERDAGANGAN INFORMAL TERHADAP PENDAPATAN KELUARGA (Studi Kasus Pedagang Eceran di Pasar Inpres Air Haji, Kecamatan Linggo Sari Baganti) - Yohana, Nova; Maryati, Sri; Malinda, Yola (Pendidikan Ekonomi, 2014)
Â ABSTRACTÂ The purpose of this research Â to analysis influence of workwomen income of infolmal trade toward family income (study cases of the retail trade in Inpres Air Haji Market, sub-district Linggo Sari Baganti).The type of this research is descriptive quantitative that used primer data. This research had done in Inpres Air Haji market, sub-district Linggo Sari Baganti on January 2014. The population in this research was retailer women with amount the sample 105 peoples where the technique of collecting the sample was. Simple random sampling.The tool to analysis the data in this research used econometric approach with multiple regression equation. The result of study showed that the variable length of education (X1), the of hours work of repiler women (X3) and the namber of family dependents (X4), in partial have positive influence and significance toward womanâs retailer income in Inpres Air Haji market, Sub-district of Linggo Sari Baganti, where as variable of age (X2) in partial havenât significance influence toward womanâs retailer income Inpres air Haji market, Sub-district Linggo Sari Baganti. In general, all variables were researched have significance influence toward woman retailer in Inpres Air Haji market, Linggo Sari Baganti. This, the income of repiler income have positive red significance offocr on family income inÂ Inpres Air Haji market, Linggo Sari Baganti.Keywords: workwomen income, length education, age, hours worked, namber family. Â Â